<span>(1_2/6 + 1_7/12):1_47/54+(1_2/9-1_7/12)*5_7/13=-89/202
1 3 5 2 4
1) 1_2/6 + 1_7/12= 1_4/12 + 1_7/12 = 2_11/12
2) 1_2/9-1_7/12=1_8/36 - 1_21/36 = -13/36
3) 2_11/12 :1_47/54= 35/12 : 101/54 = (35*54) / (12*101) = 35*9 / 2*101 = 315/202
4) -13/36 * 5_7/13 = -13/36 * 72/13 = - (13*72) / (36*13) = -2
5) 315/202 -2 = -2+1_113/202 = -89/202
</span>
Чтобы это решить надо умножить на общий знаменатель правую и левую части уравнения
4)38-12x-13=3
x=22/12
5)501-81x-99=263
x=139/81
6)113-52+36x=35
x=-13/18
1. 62м 30 см : 35 = 6230см: 35= 178 см 2. 53м 90 см : 70 = 5390 см : 70 = 77 см 3. 178 см - 77 см = 101 см или 1 м и 1 см
9-(1 целая 25/40+6/40)=9- 1 целая 31/40 =8 целых 40/40- 1 целая 31/40=7 целых 9/40=7,225
18х-3=18х+2
х=5
2)2,8-7х=15-7х-12,2
х=0